Analisis Portofolio Optimal Perusahaan Terdaftar di IHSG dengan Metode CAPM dan Markowitz - Rahma Suci Hidayati (Universitas Islam Negeri Raden Mas Said Surakarta, 2018)
The research aims to analyse the most optimal portfolio models from the various companies listed on the IDX with CAPM and Markowitz methods. With a descriptive quantitative approach, the study described the optimal portfolio models calculated using CAPM and Markowitz methods. A total of 9 companies were selected as samples with purposive technique. The results of this study show that 9 companies can form an optimal portfolio either by CAPM method or by Markowitz method.Keywords: Markowitz, Capital Asset Pricing Model, optimal portofolio